Revisiting the Financial Development and Poverty Reduction Nexus for Sub-Saharan African Countries: Evidence from Causality Tests in the Time and Frequency Domains - Keho, Yaya (International Journal of Economics and Financial Issues, 2016)
This study reexamines the causal relationship between financial development and poverty reduction for six African countries. To that end, we employ the Granger causality tests in the time and frequency domains. The results from time domain causality analysis indicate that financial development does not causes poverty reduction directly, but poverty reduction causes financial deepening in Nigeria and South Africa. While the frequency domain analysis shows evidence of bidirectional causality between financial development and poverty reduction for Cameroon in long run, and causality from finance to poverty reduction for Gabon in long term. Furthermore, causality from poverty reduction to financial development exists for Nigeria both in short and medium terms and for South Africa over the short, medium and long terms. Keywords: Poverty reduction, financial development, frequency domain analysis, Sub-Saharan Africa JEL Classifications: C32, G21, I30, O55